Evaluation of Knowledge and Skills of Patients With Asthma and COPD in Using Inhaled Therapy. Issue 4 (10th July 2020) - Gundogdu, Nevhiz; Benlier, Necla
Abstract : This study aimed to evaluate knowledge and skills in the use of inhaler devices in patients with asthma and chronic obstructive pulmonary disease who presented to our clinic for the first time. The patients were enrolled in the study by a pulmonologist. All patients were asked to demonstrate how they used their inhaler device and were assigned scores for their performance. A total of 108 patients were enrolled in the study. Discus (36.1%) and Aerolizer (31.5%) were the most commonly used devices. Patients of both sexes made more errors in the 2 steps of inhaler use (putting the device into the mouth and holding breath after inhalation) in comparison to other steps, with no significant sex difference (49.1% of the females, 62.7% of the males; P =0.15 and 0.62, respectively). Higher education level was associated with higher total scores, greater dexterity, and perceived therapeutic benefit in relation to the correct use of the inhaler device ( P <0.001, 0.006, and 0.017, respectively). No statistically significant differences were observed in total scores, ease of use of the device, and perceived benefit from treatment in relation to the inhaler device used ( P =0.148, 0.114, and 0.994, respectively). No significant impact of the initial training provider was found on total scores, ease of use, and perceived therapeutic benefit ( P =0.073, 0.201, and 0.292, respectively). Total scores, ease of use, and perceived therapeutic benefit increased with higher level of education. However, the person providing education on the inhaler technique had no significant impact on these variables.